2013
DOI: 10.1021/jf304010n
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cooking Technique on Polychlorinated Biphenyl and Polychlorinated Dioxins/Furan Concentrations in Fish and Fish Products with Intake Estimates

Abstract: Polychlorinated biphenyl (PCB) and polychlorinated dibenzo-p-dioxin (PCDD) and dibenzofuran (PCDF) concentrations were determined in composites of 18 different fish products and were prepared as raw, baked, boiled, and fried. ∑PCB concentrations were found to range from 0.12 ng·g(-1) whole weight (ww) in raw octopus to 33 ng·g(-1) ww in baked mackerel. Boiled monkfish was found to have the lowest ∑PCDD/F concentrations (0.41 pg·g(-1) ww), while maximum concentrations were observed in fried catfish (59 pg·g(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Removing the fatty skin and broiling or baking rather than frying fish may decrease exposure. 140,141 MeHg, in contrast, tends to be stored in protein rather than in fat and is distributed throughout the flesh of the fish. Thus, removing the skin or fatty tissue does not reduce mercury exposure.…”
Section: Toxicant Avoidancementioning
confidence: 99%
“…Removing the fatty skin and broiling or baking rather than frying fish may decrease exposure. 140,141 MeHg, in contrast, tends to be stored in protein rather than in fat and is distributed throughout the flesh of the fish. Thus, removing the skin or fatty tissue does not reduce mercury exposure.…”
Section: Toxicant Avoidancementioning
confidence: 99%
“…Other studies have found associations between fried seafood (shellfish or fish) intake and adverse health outcomes (e.g., diabetes [52], cancer [53], all-cause and cardiovascular mortality [54,55]), even when overall associations with total seafood intake showed no association [52,54] or non-fried seafood showed beneficial effects [56]. There is some evidence that the preparation of seafood influences the extent to which contaminants are retained in the flesh of the seafood [57][58][59][60][61]. These studies suggest that frying seafood, particularly fatty seafood harvested from contaminated waters, is potentially harmful because it can seal in organochlorines and other chemical pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the constant lack of a Polish database of concentrations of dioxins and related compounds in food products, the FDA assessment of dioxins in food was mainly used, although whenever possible, Polish data were used, such as in the case of some fish species [10,11,12,13]. Final concentrations were calculated for each individual and expressed in pg TEQ per kilogram of body weight per day.…”
Section: Materials and Methiodmentioning
confidence: 99%